Differences and driving factors of leaf functional traits between old tree and mature tree of Pinus tabulaeformis in the Loess Plateau - Yuting Lei; Zimao Feng; Zhong Zhao (BMC Plant Biology)
Abstract Background Study the leaf functional traits is highly important for understanding the survival strategies and climate adaptability of old trees. In this study, the old (over 100 years old) and mature trees (about 50 years old) of Pinus tabulaeformis in the Loess Plateau were studied, and the variation of 18 leaf functional traits (6 economic, 4 anatomical, 2 photosynthetic and 6 physiological traits) was analyzed to understand the differences of survival strategies between old and mature trees. Combined with transcriptome and simple sequence repeats (SSR) techniques, the effects of soil property factors and genetic factors on leaf functional traits and the potential molecular mechanisms of traits differences were studied. Results Compared with mature trees, old trees presented greater economic traits (except leaf phosphorus content), anatomical traits (except the stomatal density), and physiological traits (except superoxide dismutase activity) and lower photosynthetic traits, and their survival strategies were more conservative. The difference was mainly driven by soil property and genetic factors (common explanation rate was 67.89%), and the independent effect of genetic factors (10.09%) was slightly higher than that of soil property factors (2.88%). In addition, by constructing weighted gene co-expression networks analysis WGCNA), this research identified 24 candidate hub genes that regulate leaf functional traits, most of which are related to plant growth and development and the stress response, and can be used for further regulatory mechanism analysis. Conclusions In conclusion, this study is helpful to understand the ecological adaptability of P. tabuliformis under the background of climate change in the Loess Plateau, and provides a theoretical basis related to leaf functional traits and molecular regulation for the protection of old trees.